Emotional Dimensions of Conversion: An African Evangelical Congregation in Montreal - Mossière, Géraldine (Anthropologica, 2022)
Drawing on fieldwork conducted in an African evangelical congregation in Montreal, I examine the conversion narrative of a new member. I show that experience of ritual performance is a key element in her trajectory. Various techniques of ritual are used to create an emotional atmosphere that shifts the frame of perception, preparing the would-be member to accept a new system of meaning and a new sense of belonging. In this setting, the "somatic mode of attention" gives rise to a new process of subjectivation which involves the recoding, transformation and purification of the body, the spirit and the self.